Pengaruh Price To Book Value, Inflasi, Nilai Kurs dan Suku Bunga Terhadap Return Saham - Dewi Badi’atuzzulfa; Putri Awalina; Imarotus Suaidah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of Price to Book Value (PBV), inflation, exchange rates, and interest rates on stock returns in food and beverage sector companies listed on the Indonesia Stock Exchange during the period 2020 to 2022. This research uses a quantitative approach with secondary data obtained from company financial reports and macroeconomic indicators published by authorized institutions. The population in this study consisted of 26 companies, while the sample included 17 companies selected through judgment sampling technique over a period of 3 years, resulting in 51 observations. The data analysis methods used include classical assumption tests to ensure the validity of the regression model, multiple linear regression analysis to examine the relationship between variables, and hypothesis testing using t-test (partial) and F-test (simultaneous).The results of the t-test show that each of the independent variables—Price to Book Value, inflation, exchange rate, and interest rate—has a significant influence on stock returns when tested individually. Furthermore, the F-test results demonstrate that these four variables simultaneously have a significant effect on stock returns in the food and beverage sector. These findings suggest that both company-specific financial ratios and macroeconomic factors play an important role in determining investor returns in this industry. Therefore, investors and policymakers should take these variables into account when making decisions related to investment strategies and economic policy in the capital market, especially during times of economic uncertainty.